Efficacy and safety of fluocinolone acetonide 0.025% otic solution in patients with otic eczema: a randomized, double-blind, placebo-controlled clinical trial. Issue 10 (October 2018) - Montoro, Victoria; Asensio, Carlos; Martínez, Ángel; Lorente, Juan; Rodríguez, Francisco J.; Montojo, José; Gavilanes, Javier; Sarría, Pedro; Langdon, Cristóbal; Prades, Eduard
Objectives: To assess the efficacy and safety of fluocinolone acetonide 0.025% otic solution versus placebo in treating patients with otic eczema. Methods: In this multicentre, randomized, double-blind, parallel-group phase 3 clinical trial, conducted at 12 Spanish centres between March 2012 and March 2013, patients received fluocinolone acetonide 0.025% or placebo otic solution twice daily for 7 days (days 1–7) with an 8-day follow-up (days 9–15). Outcome measures included change in itching from baseline (day 1) to study days 4–8 and 9–15, and change in otoscopic signs (erythema, oedema, and scaling) from baseline to the end of treatment (day 8) and end of follow-up (day 15). Results: Patients treated with fluocinolone acetonide 0.025% (n = 66), as compared with placebo-treated patients (n = 69), showed significantly higher reductions in itching from baseline to study days 4–8 and 9–15, and in individual and global otoscopic signs from baseline to the end of treatment (day 8) and end of follow-up (day 15). Incidence and severity of adverse events was similar between the fluocinolone and placebo groups. Conclusions: Fluocinolone acetonide 0.025% otic solution, administered twice daily for 7 days, is an effective and safe treatment for otic eczema.